Stress tolerant crop varieties of major arid zone crops to promote resilience to climatic stresses - Solanki, R. K.; Mahla, H. R.; Kakani, R. K.; Choudhary, K. B.; Sharma, R. (Indian Farming, 2018)
Crops like pearl millet, moong bean, moth bean and cluster bean are integral part of the arid agricultural system. Pearl millet being the key fodder and grain crop has high acreage; early hybrid varieties are available which suits well under limited moisture and high temperature stress. Moong bean and moth bean are essential for sustainability and nutrient replenishment in nutrient poor soils of the region, though the crop acreage of moth bean is decreasing over the years which seem replaced by moong bean. Cluster bean occupied the place of an industrial cash crop for its valuable gum present in seed. India being the leader in cluster bean gum production, supports the sustainable demand from arid region. Varieties contributed significantly in increasing the yield and productivity of these crops in the region.